2019
DOI: 10.1101/mcs.a003491
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing for early-onset or atypical dementia: high diagnostic yield and frequent observation of multiple contributory alleles

Abstract: We assessed the results of genome sequencing for early-onset dementia. Participants were selected from a memory disorders clinic. Genome sequencing was performed along with C9orf72 repeat expansion testing. All returned sequencing results were Sanger-validated. Prior clinical diagnoses included Alzheimer's disease, frontotemporal dementia, and unspecified dementia. The mean age of onset was 54 (41–76). Fifty percent of patients had a strong family history, 37.5% had some, and 12.5% had no known family history.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 57 publications
4
37
0
Order By: Relevance
“…Several studies have suggested that ADAM10 gene is potentially involved in the development of neurodegenerative disorders 26–29 . Though an earlier published negative report indicated the lack of association between ADAM10 and AD, 30 a reasonable explanation for this inconsistency might be based on SNP variations and sample characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that ADAM10 gene is potentially involved in the development of neurodegenerative disorders 26–29 . Though an earlier published negative report indicated the lack of association between ADAM10 and AD, 30 a reasonable explanation for this inconsistency might be based on SNP variations and sample characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Besides atherosclerosis, TNK1 also participates in several other diseases, such as atypical dementia, Alzheimer's Disease, and colorectal cancer [ 17 19 ]. In the trauma-induced intestinal injury and multiorgan failure, TNK1 induces cell apoptosis and the release of proinflammatory factors, IL-6 and TNF- α .…”
Section: Discussionmentioning
confidence: 99%
“…AD is an adult-onset age-dependent disease that worsens over time. While TM2D3 p.P155L has been associated with LOAD (Jakobsdottir et al, 2016) and TM2D3 p.P69L has been recently reported in a proband with EOAD or frontotemporal dementia (Cochran et al, 2019), there is no functional data that directly links this gene to an age-dependent neurological phenotype in any species. To determine if loss of TM2D3 causes an age-dependent phenotype, we first assessed the lifespan of amx D mutant animals.…”
Section: Amx Null Mutants Have Shortened Lifespanmentioning
confidence: 99%
“…This showed that the function of TM2D3 is evolutionarily conserved between flies and humans, and the molecular function of TM2D3 that is relevant to LOAD may also be related to Notch signaling. More recently, another rare missense variant (p.P69L) in this gene has been reported in a proband that fit the diagnostic criteria of EOAD or frontotemporal dementia (Cochran et al, 2019), indicating that other TM2D3 variants may be involved in dementia beyond LOAD.…”
Section: Introductionmentioning
confidence: 99%